Source-sink dynamics of coral larvae: implications for ecosystem management in Pahang - Mohd. Hanapiah, Muhammad Faiz; Mustapa, Mohd Zaini (UTS Publisher, 2025)
Understanding coral larvae dispersal and connectivity is vital for effective ecosystem management and habitat restoration. This study investigates the source-sink dynamics of coral larvae between Marine Protected Areas (MPAs) and nearshore reefs in the Pahang coastal region, Malaysia. Using a biophysical model integrating the Lagrangian particle tracking module with the MIKE 21 FM hydrodynamic model, we simulated dispersal pathways of Acroporid larvae during a spawning event in April 2021. Results revealed northward larvae movement, influenced by prevailing currents, with significant retention within MPAs during the initial dispersal phase (2–6 days). Optimal dispersal (6–8 days) saw broader connectivity, while prolonged dispersal (18–20 days) demonstrated potential for larvae to reach nearshore reefs in southern Pahang. Nearshore reefs, particularly in southern Kuantan, were identified as critical sink sites, emphasizing their importance in ecosystem management strategies. This study highlights the role of MPAs as larvae sources and highlights the interconnectedness of reef systems in supporting coral population sustainability. These findings provide a framework for prioritizing conservation efforts, ensuring resilient reef networks amid environmental challenges.